Gary Alan Fine – Véronique Campion-Vincent – Chip Heath (eds.): Rumor Mills. The Social Impact of Rumor and Legend.: Transaction, New Brunswick 2005. - Janeček, Petr (Lidé města, 2008)
A review of the book by Gary Alan Fine, Véronique Campion-Vincent and Chip Heath.